2011
DOI: 10.1007/s11746-011-1777-0
|View full text |Cite
|
Sign up to set email alerts
|

Binary Phase Behavior of Diacid 1,3‐Diacylglycerols

Abstract: Fifteen phase diagrams were prepared using data from differential scanning calorimetry analysis of binary blends of representative diacid 1,3-DAG. The behavior observed in binary phase diagrams is related to the difference in T m (DT m ) between system components-eutectic for DT m \ 26°C and monotectic for DT m [ 30°C. Binary blends were prepared using six diacid 1,3-DAG: 1and 1,3-palmitoyl-oleoyl-rac-glycerol. Diacid 1,3-DAG were synthesized using representative FA: hexanoic (6:0)-shortchain FA; lauric (12:0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…Below the solid transition line, the C31 SS changed from a rotator to an orthorhombic modification. The predominantly monotectic behavior of this mixture was consistent with the behavior shown by binary mixtures of triacylglycerols [16] and mixtures of diacylglycerols [17] in which the difference between the melting temperatures of the system components (ΔT M ) was close to or above 20 °C. On the other hand, mixtures of n-tetracosane/stearic acid (ΔT M ≈ 19 °C) had a eutectic phase diagram and solid solutions (only one melting endotherm was evident) at mole fractions below 0.15 stearic acid [6].…”
Section: Resultssupporting
confidence: 80%
“…Below the solid transition line, the C31 SS changed from a rotator to an orthorhombic modification. The predominantly monotectic behavior of this mixture was consistent with the behavior shown by binary mixtures of triacylglycerols [16] and mixtures of diacylglycerols [17] in which the difference between the melting temperatures of the system components (ΔT M ) was close to or above 20 °C. On the other hand, mixtures of n-tetracosane/stearic acid (ΔT M ≈ 19 °C) had a eutectic phase diagram and solid solutions (only one melting endotherm was evident) at mole fractions below 0.15 stearic acid [6].…”
Section: Resultssupporting
confidence: 80%
“…Phase diagrams were constructed using the onset temperature (T on ) of the lowest melting peak and the peak temperature (T p ) of the highest melting peak to represent an approximation of the onset and completion of the melting process [23]. Phase diagrams were constructed using the onset temperature (T on ) of the lowest melting peak and the peak temperature (T p ) of the highest melting peak to represent an approximation of the onset and completion of the melting process [23].…”
Section: Experimental Pseudo-phase Diagrammentioning
confidence: 99%
“…A phase diagram shows the different phases (solid, liquid, or gas) of materials at equilibrium as a function of temperature and composition, and sometimes of 1 3 pressure. The use of phase and pseudo-phase diagrams in food systems has been reported by several researchers [19][20][21][22][23][24]. Binary phase diagrams are typically constructed by blending different proportions of two pure components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the number of individual polymorphic forms, molecular structures, melting and crystallization properties and other important polymorphic properties drastically differed from one TAG to others, when the fatty acid moiety at the at the sn-3 position varied. Recently, Craven and Lencki extensively studied mixtures of chiral mixed-acid DAG and TAG, in which varying fatty acid moieties (saturated fatty acids differing in carbon number, and unsaturated fatty acid) are asymmetrically connected to the glycerol [18][19][20][21][22]. They showed that critical differences in the occurrence of the stable polymorphic forms and crystallization behavior were observed between the optical isomers and racemic mixtures.…”
Section: Introductionmentioning
confidence: 99%